Elevated remnant cholesterol impairs sleep characteristics in individuals with newly diagnosed moderate-to-severe obstructive sleep apnea: a cross-sectional case–control study - Liu, Yanling; Zhang, Fengying; Zhang, Ping; Chen, Li (Frontiers in Neurology, 2025)
BackgroundAlthough obstructive sleep apnea (OSA) is widely recognized as a common contributor to disruptions in sleep and lipid metabolism, there is still a lack of concrete evidence to substantiate this correlation. Remnant cholesterol (RC) is increasingly being acknowledged as a lipid-related risk factor for many diseases; however, its role in sleep remains uncertain. We aimed to assess whether RC is associated with OSA disease events and to determine the impact of RC on sleep parameters.MethodsThis cross-sectional case–control study recruited141patients recently diagnosed with moderate-to-severe OSA (based on overnight polysomnography) and 47 healthy participants who served as controls. We performed a PSG assessment and collected sleep parameters and biochemical, demographic, and clinical data.ResultsCompared to controls (19.1%), patients with OSA exhibited a significantly higher prevalence of elevated RC (36.1%). Patients with OSA had higher serum RC levels than controls [0.37 (0.19–0.56) vs. 0.45 (0.255–0.78) mmol/L; p = 0.013]. Compared to patients with OSA without elevated serum RC, those with high RC levels exhibited statistically significant differences in wake frequency; the percentage time in non-rapid eye movement stage 1 (NREM1, N1), N2%, and N3 sleep; Apnea-Hypopnea Index (AHI); Oxygen Desaturation Index (ODI); Breathing-related arousal index. (BAI); and average SpO2. Pearson correlation analysis showed that the serum RC concentration in patients with OSA was positively correlated with wake frequency, percentage time in N1, AHI, ODI, and BAI, whereas it was negatively correlated with percentage time in N2 and N3 and mean nocturnal oxygen saturation.ConclusionFor the first time, we found that elevated RC levels are highly prevalent and significantly associated with impaired sleep architecture and respiratory parameters in patients with newly diagnosed OSA. Therefore, serum RC assessment should be included in the work-up for the diagnosis of OSA.